2020
DOI: 10.1101/2020.01.08.898817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mediodorsal and ventromedial thalamus engage distinct L1 circuits in the prefrontal cortex

Abstract: 150 Introduction: 630 Results: 3,236 Discussion: 1,357 Figures: 8 + 8 supplementary figures + 2 supplementary tables ACKNOWLEDGEMENTSWe thank the Carter lab for helpful discussions and comments on the manuscript. This work was supported by NIH T32 GM007308 (DPC) and NIH R01 MH085974 (AGC).

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 71 publications
7
40
1
Order By: Relevance
“…On the other hand, it is rather straightforward that the inhibitory projection to the STN (and substantial pars reticulata) mediates the motor-promoting effects, and it is consistent with the established relationship between STN activity and movement suppression (Verhulst, 1976;Hamani et al, 2004;Aron and Poldrack, 2006;Aron et al, 2007;Eagle et al, 2008;Schmidt et al, 2013;Schweizer et al, 2014;Fife et al, 2017;Wessel and Aron, 2017). In addition to the established literature demonstrating that the GPe sends inhibitory signals to the input and output nuclei of the basal ganglia (Jessell et al, 1978;Mink, 1996;Smith et al, 1998;Kita, 2007;Hegeman et al, 2016), recent studies highlight the existence of cortico-pallido-cortical loops (Saunders et al, 2015;Schwarz et al, 2015;Ahrlund-Richter et al, 2019;Karube et al, 2019;Abecassis et al, 2020;Anastasiades et al, 2020;Clayton et al, 2020), though the precise circuit entities involved have yet to be defined. The direct feedback from Npr3 + (aka Npas1 + -Nkx2.1 + ) neurons to cortical regions (Figure 1c, see also (Abecassis et al, 2020)) argues that the action selection is not simply a top-down command.…”
Section: Gpe Neuron Diversitysupporting
confidence: 70%
“…On the other hand, it is rather straightforward that the inhibitory projection to the STN (and substantial pars reticulata) mediates the motor-promoting effects, and it is consistent with the established relationship between STN activity and movement suppression (Verhulst, 1976;Hamani et al, 2004;Aron and Poldrack, 2006;Aron et al, 2007;Eagle et al, 2008;Schmidt et al, 2013;Schweizer et al, 2014;Fife et al, 2017;Wessel and Aron, 2017). In addition to the established literature demonstrating that the GPe sends inhibitory signals to the input and output nuclei of the basal ganglia (Jessell et al, 1978;Mink, 1996;Smith et al, 1998;Kita, 2007;Hegeman et al, 2016), recent studies highlight the existence of cortico-pallido-cortical loops (Saunders et al, 2015;Schwarz et al, 2015;Ahrlund-Richter et al, 2019;Karube et al, 2019;Abecassis et al, 2020;Anastasiades et al, 2020;Clayton et al, 2020), though the precise circuit entities involved have yet to be defined. The direct feedback from Npr3 + (aka Npas1 + -Nkx2.1 + ) neurons to cortical regions (Figure 1c, see also (Abecassis et al, 2020)) argues that the action selection is not simply a top-down command.…”
Section: Gpe Neuron Diversitysupporting
confidence: 70%
“…We found that CCK+ interneurons make robust inhibitory connections onto neighboring pyramidal cells in L5 of IL PFC. Importantly, these connections are much stronger onto PT cells, similar to our previous findings for PV+, SOM+, and NDNF+ interneurons ( Anastasiades et al, 2020 ; Anastasiades et al, 2018 ). Biased inhibition is thus a general property of inhibitory connections in the PFC, although strength also depends on intrinsic properties ( Anastasiades et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…We found CCK+ inputs are highly restricted to the somatic compartment of both IT and PT cells ( Figure 4—figure supplement 1B & D ). Therefore, in contrast to the strong dendritic innervation by SOM+, 5HT3aR+, and NDNF+ cells ( Anastasiades et al, 2020 ; Marlin and Carter, 2014 ), these results indicate that CCK+ inputs are primarily near the soma of IT and PT cells.…”
Section: Resultsmentioning
confidence: 66%
“…Matrix cells outnumber core cells but are comparatively understudied (Rubio-Garrido et al, 2009). Contrary to their original classification by Lorento de No as “nonspecific” (Lorento de No, 1938), distinct matrix nuclei project to specific cortical regions with sublaminar specificity (Anastasiades et al, 2020; Cruikshank et al, 2012; Yamawaki et al, 2019b). These projections result in subtype-specific activation of cortical inhibitory neuronal subtypes, both in layer 1 (Anastasiades et al, 2020; Cruikshank et al, 2012) and in deeper layers (Delevich et al, 2015), to provide temporally precise regulation of cortical activity (Cruikshank et al, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Contrary to their original classification by Lorento de No as “nonspecific” (Lorento de No, 1938), distinct matrix nuclei project to specific cortical regions with sublaminar specificity (Anastasiades et al, 2020; Cruikshank et al, 2012; Yamawaki et al, 2019b). These projections result in subtype-specific activation of cortical inhibitory neuronal subtypes, both in layer 1 (Anastasiades et al, 2020; Cruikshank et al, 2012) and in deeper layers (Delevich et al, 2015), to provide temporally precise regulation of cortical activity (Cruikshank et al, 2012). These inputs also target excitatory neurons (Collins et al, 2018; Cruikshank et al, 2012; Guo et al, 2018; Rodriguez-Moreno et al, 2020; Rubio-Garrido et al, 2009; Van Der Werf et al, 2002; Yamawaki et al, 2019b).…”
Section: Introductionmentioning
confidence: 85%